Uncovering Anti-Obesity Candidates from Robusta Green Coffee: In Silico Evaluation of Bioactive Compounds Targeting PPAR-α - Mahardika, Bintang Satrio; Putri, Viona Algesia Fiola; Putri, Yolla Adellia; Jasimah, Jasimah; Gabriel, Kevin; Rusdin, Agus; Novitasari, Dhania (Journal of Pharmaceuticals and Natural Sciences, 2025)
Obesity arises from a chronic imbalance between energy intake and expenditure, leading to excessive accumulation of body fat. Peroxisome proliferator-activated receptor-alpha (PPARα) plays a key regulatory role in lipid metabolism, particularly in reducing the de novo synthesis of fatty acids. Robusta coffee has been widely consumed as part of the lifestyle, yet scientific evidence for its pharmacological effects is limited. This study aimed to evaluate the molecular interactions between secondary metabolites from Green Bean Coffee Robusta (Coffea canephora P.) and PPARα using in silico approaches. The workflow included screening compounds from C. canephora based on Lipinski’s Rule of Five (RO5) and ADMET predictions, followed by pharmacophore modelling and molecular docking simulations using AutoDock against PPARα (PDB ID: 2P54). All the bioactive constituents in C. canephora met the requirements of RO5, and several metabolites were assessed based on their pharmacokinetic profile and toxicology prediction. Further molecular docking analysis identified 4-ethyl-2-methoxyphenol as the most promising anti-obesity candidate, demonstrating the lowest binding energy (-4.58 kcal/mol) and an inhibition constant of 440.47 µM. The compound formed key hydrogen bonds with amino acid residues ALA333, THR279, CYS276, and CYS275. These findings suggest that 4-ethyl-2-methoxyphenol from Green Bean Coffee Robusta exhibits potential as an anti-obesity agent through its interaction with the PPARα receptor. Further in vitro and in vivo studies are required to validate its pharmacological effects.